Dietary Intake and Physical Activity of Normal Weight and Overweight/Obese Adolescents - Dina D'Addesa; Laura D'Addezio; Deborah Martone; Laura Censi; Alessandra Scanu; Giulia Cairella; Amedeo Spagnolo; Ettore Menghetti (International Journal of Pediatrics)
Purpose. To evaluate the relationship between overweight/obesity and dietary/lifestyle factors among Italian adolescents. Methods. On a total of 756 adolescents with mean age 12.4±0.9, body mass index, food consumption, and time dedicated to after school physical activities and to TV viewing were determined. The data were analysed according to age, nutritional status, and gender. The analysis of variance and multiple logistic regression analysis were performed to investigate the association between dietary/lifestyle factors and overweight/obesity. Results. The percentages of overweight and obesity were, respectively, 28% and 9% among boys, 24% and 7% among girls. The overweight/obesity condition in both genders was associated with parental overweight/obesity (𝑃<.001 for mother), less time devoted to physical activity (𝑃<.001 for boys and 𝑃<.02 for girls) and being on a diet (𝑃<.001). Direct associations were also observed between BMI and skipping breakfast and the lower number of meals a day (boys only). Conclusions. This pilot study reveals some important dietary and lifestyle behaviour trends among adolescents that assist with identification of specific preventive health actions.